THE EFFECTS OF SNAKEHEAD FISH PROTEIN CONCENTRATE (Channa striatus) ADDITION ON THE QUALITY OF KWETIAU - Wiwi Solvia Siahaan; N Ira Sari; Suardi Loekman (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
The research aims to understand the addition effects of snakehead fish(Channa striatus) protein concentrate toward kwetiau quality, that is known theaddition of fish protein concentrate efficient in make of kwetiau. Design used inthis study was completely randomized design (CRD) non factorial, with fourthlevels of treatment that was without the addition of snakehead fish proteinconcentrate (K0), the addition of snakehead fish protein concentrate 5% (K5),the addition of snakehead fish protein concentrate 10% (K10), and the addition ofsnakehead fish protein concentrate 15% (K15). The experiments were performedthree times repetitions, and produced 12 units. The organoleptic test result basedon tested parameter that K0 was the best treatment with characteristics such white,attractive, chewy texture, sticky and soft, wet kwetiau aroma ( aroma like flour )but with additon of 5% snakehead fish protein concentrate could increase proteincontent, but kwetiau taste did not change, decrease the amount of water contentand microbial. Water content (63.45%), protein content (12.95%), ash content(1.82%), total bacterial colonies (7,4 X 104 sel/g), and elongationconsecutively(27.22%)Keywords: Kwetiau, rice flour, snakehead fish, snakehead fish protein concentrate